2017
DOI: 10.1017/s0031182017002128
|View full text |Cite
|
Sign up to set email alerts
|

Environmental determinants of haemosporidian parasite prevalence in a declining population of Tree swallows

Abstract: The prevalence of vector-borne parasites such as haemosporidian species is influenced by several environmental factors. While the negative effects of parasitism on hosts are well documented, these can also be amplified by interactions with environmental stressors, many of which are anthropogenic. Yet, we know little about the possible effects of anthropogenic perturbations on parasite prevalence. The goals of this study were to assess the prevalence and environmental determinants of haemosporidian parasites in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 108 publications
(174 reference statements)
1
11
0
Order By: Relevance
“…Water is essential for aquatic larval development of vectors, and topographic features that increase surface water persistence promote increased abundance (Ferraguti et al, 2016;Ganser et al, 2016;González-Quevedo, Davies, & Richardson, 2014). In addition, anthropogenic factors such as habitat degradation, agriculture, and urbanization can all influence malaria dynamics (González-Quevedo et al, 2014;Turcotte, Bélisle, Pelletier, & Garant, 2018;Yanoviak, Paredes, Lounibos, & Weaver, 2006). Together, these factors have the potential to shape fine-scale spatial structuring in pathogen selection pressures and host immunogenetic variation.…”
Section: Introductionmentioning
confidence: 99%
“…Water is essential for aquatic larval development of vectors, and topographic features that increase surface water persistence promote increased abundance (Ferraguti et al, 2016;Ganser et al, 2016;González-Quevedo, Davies, & Richardson, 2014). In addition, anthropogenic factors such as habitat degradation, agriculture, and urbanization can all influence malaria dynamics (González-Quevedo et al, 2014;Turcotte, Bélisle, Pelletier, & Garant, 2018;Yanoviak, Paredes, Lounibos, & Weaver, 2006). Together, these factors have the potential to shape fine-scale spatial structuring in pathogen selection pressures and host immunogenetic variation.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, measuring infection status after mate choice has occurred likely gives a good picture of this aspect at the time mating choices were made. It is probable, however, that some of the infections occurred on the breeding grounds, as we previously showed that local transmission is present in this study system ( Turcotte et al, 2018 ). This local transmission could also drive to some extent the non-random distribution of infected individuals we reported here.…”
Section: Discussionmentioning
confidence: 67%
“…While mate choice patterns are occurring prior to the sampling for infection, most of the infections detected are probably chronic ( Turcotte et al, 2018 ). Hence, measuring infection status after mate choice has occurred likely gives a good picture of this aspect at the time mating choices were made.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A common thread among many of the studies included here is that anthropogenic changes to landscapes have a marked effect on diversity and community composition. Turcotte et al (2017) addressed this explicitly by examining the environmental predictors of parasite prevalence across human-modified habitats in a population of tree swallows that is in documented decline. The authors examined the potential for environmental stressors, using three habitats that varied in their level of anthropogenic influence, to amplify effects of parasitism.…”
mentioning
confidence: 99%